Penertiban Juru Parkir Liar di Kecamatan Tampan Kota Pekanbaru - Lina Sari; Zulkarnain Zulkarnain (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Parking attendants without permits in parking operations are one of the many legal problems faced by motorists in Pekanbaru. When compared with other sub- districts in Pekanbaru City, Tampan Sub-district has the largest population, reaching 25.27% of the city's total population. And there is data showing that there are still a large number of illegal (illegal) parking attendants. So the aim of this research is to find out how to control illegal parking attendants in Tampan District, Pekanbaru City and what are the obstacles to controlling illegal parking attendants in Tampan District, Pekanbaru City. data collection in the form of interviews, observation and documentation. The type of research used in this research is qualitative and the data analysis techniques used are data collection, data reduction, data presentation and drawing conclusions. In the implementation of controlling illegal parking attendants in the city of Pekanbaru, it is still not optimal and there are still many illegal parking spots that occur. Inhibiting factors in controlling illegal parking in Tampan District, Pekanbaru City are caused by minimal operational costs, lack of personnel in controlling parking, lack of public awareness and compliance.